Genetic diversity and rhizome flesh color variation among indonesian turmeric (Curcuma longa L.) accession revealed by SSR markers - Amien, Suseno; Anggraeni, Marisa; Karuniawan, Agung; Wicaksana, Noladhi (Universitas Padjadjaran, 2026)
Turmeric (Curcuma longa L.) is a rhizomatous plant widely cultivated in Indonesia. Although recent studies have demonstrated that simple sequence repeat (SSR) markers are highly effective for assessing genetic diversity in Curcuma longa germplasm, most investigations have focused either on molecular diversity or breeding-oriented germplasm characterization traits of agronomic without integrating phenotypic commercial importance, particularly rhizome flesh color. The study was conducted from February to May 2026. This study aimed to evaluate the genetic diversity, phylogenetic relationships, and rhizome flesh color variation among Indonesian turmeric accessions collected by Plant Breeding Laboratory at the Faculty of Agriculture, Universitas Padjadjaran, and was grown at the Ciparanje Experimental Farm. Eighteen turmeric accessions from various locations in Indonesia were analyzed using six SSR markers to assess genetic variation and phylogenetic relationships. The results showed that 12 polymorphic alleles were identified, with the highest polymorphism information content (PIC) value of 0.58 observed for the CuMiSat-35 primer. Principal coordinate analysis and cluster analysis divided the accessions into two main clusters, with Jaccard genetic distances ranging from 0.00 to 0.80, indicating genetic diversity among the 18 turmeric accessions tested. The accession pairs with the longest kinship distances were found between accession CL-93 (South Sulawesi) and several other accessions, such as CL-01, CL-20, CL-25, CL-34, CL-36, CL-38, CL-47, CL-61, and CL-84, with a Jaccard coefficient of 0.80 and a genetic similarity of 20%, indicating the presence of genetic variation. Eighteen turmeric accessions exhibited varying rhizome flesh colors, which illustrates the differences in curcumin content.